Donor-specific antibody management in intestine transplantation: hope for improving the long-term durability of the intestine allograft?. Issue 2 (April 2019) - Hawksworth, Jason S.; Matsumoto, Cal S.
Abstract : Purpose of review: In this review, we appraise the current status of donor-specific antibody (DSA) monitoring and treatment in the literature and highlight the current challenges in DSA management for the intestine transplant community. Recent findings: Sensitizing events are common in patients referred for intestinal transplant, as these patients universally are repeatedly exposed to immune activation and inflammatory events. Both preformed and de novo DSA have been shown to increase rejection and graft loss in intestine recipients. Avoidance of preformed DSA with the use of virtual crossmatch (VXM) and antibody monitoring protocols to detect and treat de novo DSA may improve intestine transplant outcomes. There is no consensus on the clinical and pathologic criteria that are required to diagnose antibody-mediated rejection (AMR) in the intestine recipient. Therefore, many clinicians treat AMR based on the coincidence of DSA and acute biopsy-proven rejection. Inclusion of the liver in the intestine allograft appears to be immunologically protective in the setting of DSA with improved outcomes and a higher rate of preformed DSA clearance. Critically, DSA has been linked to chronic rejection and poor long-term outcomes in the intestine recipient. Summary: On the basis of increasing evidence in the intestine transplant literature, it appears that avoidance of preformed DSA and aggressive monitoring and treatment of de novo DSA is a key to long-term survival following intestine transplantation.